Analysis of spatiotemporal dynamics of forest Net Primary Productivity of Nepal during 2000–2015. Issue 11 (2nd June 2020) - Koju, Upama A.; Zhang, Jiahua; Maharjan, Shashish; Bai, Yun; Zhang, Sha; Yao, Fengmei
ABSTRACT: Proper estimation and spatiotemporal trend analysis of net primary productivity (NPP) are very important for forest ecosystem monitoring and management. In this article, we investigate the spatiotemporal trend and variability of the Boreal Ecosystem Productivity Simulator (BEPS)-derived forest NPP over Nepal during the period 2000–2015. This study is the first attempt to simulate nation-wide NPP at 500 m spatial resolution at the daily step for the recent 16-year period. In our work, we use a process-based model BEPS, to estimate the NPP in the forest of Nepal. All the meteorological, forest cover, soil data, leaf area index (LAI), tree cover, biomass, and biophysical parameters, required for the model, were downloaded from different sources or prepared, pre-processed and used in the BEPS model to come up with the daily NPP. In spite of some fluctuations in NPP in some years, there is an overall positive change in the NPP throughout the study period. The annual average national NPP has been raised from 1.34 g m −2 day −1 to 1.74 g m −2 day −1 from 2000 to –2015. Examining the inter-annual variation, we found almost 87% of the total forested area has a positive inter-annual variation and 13% negative. The overall average daily NPP per m 2 over the entire forest in the entire period ranges from 0.1 to 4.7 g m −2 day −1 with an average of 1.65 g m −2 day −1 . Similarly, by physiographic regions, the average NPP in the plain was 2.43 g m −2 day −1, hills 1.83 g m −2 day −1, and mountain 1.41 g m −2 day −1 . The total daily NPP for the entire forest area ranges from 3 to 257 tons with an average of 96 tons over the study period. NPP was found to be highly influenced by rainfall, solar radiation, and temperature. While in case of the variation of NPP on different forest types, broad-leaved forest was found to have almost 1.7 times more (NPP 1.97 g m −2 day −1 ) than that of needle-leaved forest (NPP 1.18 g m −2 day −1 ). The slope per cent of <15% is favourable (NPP 2.15 g m −2 day −1 ) for higher NPP among different slope per cent. We found that this method could be more convenient for estimation and studies of the NPP in Nepal. The result from this study gives us important information on intra and inter-annual spatiotemporal trends and variability of NPP in the forest of overall Nepal of different physiographic regions. It also gives us information on the variation in trends of NPP with the change in various climatic and vegetation parameters, which can be important for the proper forest ecosystem monitoring, management, and planning operations.